Gestão de compras em um fabricante de avião: uma análise sob a perspectiva da gestão de cadeia de suprimentos flexível - Guerra, João Henrique Lopes (2011)
The influence and status that the purchasing function has gained in manufacturing companies are not reflected in the literature related to aircraft manufacturers. There are few studies that adopt, in this environment, the analysis of the purchasing function as the central theme of research. Particularly, there is a lack of studies on the challenges and problems it faces. In order to provide a contribution to this theme, an exploratory case study (single) in an aircraft manufacturer (Embraer) has been carried out aiming to identify the challenges and problems generated in its purchasing function due to the influence of the supply chain, the product (aircraft) and the dynamic environment in which the aerospace industry operates, and to analyze how they should be faced, considering the Supply Chain Management (SCM) approach and the supply chain flexibility concept. The following challenges and problems were identified: changes in customer purchase orders and in the aircraft manufacturer production plan; risks of harmed relationships with suppliers and lack of suppliers confidence on demand information; product changes; customization; late configuration; geographical dispersion and physical distance from suppliers; material acquisition lead-times; increase in production rate; disputes among customers for suppliers limited resources; bargaining power of suppliers; some potential sources of material shortage. The strategies to face them were defined based on the SCM elements (supply chain overall operational efficiency, process integration, information sharing, strategic alignment, and relationship among companies) and the supply chain flexibility dimensions (organizational, supply, market, logistics, information systems, and operations). The results reveal the importance of SCM and supply chain flexibility for the purchasing function and, by extension, for an aircraft manufacturer and the aerospace industry. They also show that SCM and supply chain flexibility can be used in a complementary and convergent way. Although the purchasing function stands at a privileged position regarding the potential of influence over business competitiveness, in the case of an aircraft manufacturer that position is also very challenging. As the aircraft manufacturers are driving their focus to some specific competencies, the challenges and problems analyzed in this research drive the purchasing function to prioritize competences related to the design and management of the supply chain.